Analyzing wave propagation problems with the improved complex variable element-free Galerkin method. (March 2019) - Cheng, H.; Peng, M.J.; Cheng, Y.M.
Abstract: Two-dimensional wave propagation problems in this paper are analyzed with improved complex variable element-free Galerkin (ICVEFG) method. Improved complex variable moving least-squares (ICVMLS) approximation is applied to construct the shape function, and modified Galerkin weak form of wave propagation problems is used for obtaining the final system equations, then all equations of ICVEFG method for wave propagation problems are obtained. The convergences of ICVEFG method about node distribution and time step are analyzed, and the influences of weight functions, scale parameter of the influence domain and penalty factor on the numerical solutions are discussed. Example problems show that ICVEFG method has higher computational speed with higher precision.